2002
DOI: 10.1108/00070700210435380
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and challenges for developing countries in trade and production of organic food and fibers

Abstract: Especially after the Second World War, both in developed and to some extent developing countries, agriculture became highly mechanized and specialized as well as heavily dependent on agro‐chemicals. Such intensification of farming has produced higher yields and greater wealth but has also created some problems affecting the environment, food and farm‐worker safety. Today, different farming systems are subject to discussion and research to discover an alternative to this current agriculture such as organic prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 6 publications
0
25
0
4
Order By: Relevance
“…Further, it was found that even though farmer movements and environmentalists concerns propagated the policy level changes (Zygmont, 2000), the real impetus that drove farmers to adopt organic farming practices was largely driven by consumer demands (Rehber and Turhan, 2002).Hence, it is critical to understand the consumers who are committed organic consumers.…”
Section: Organic Food Consumption: Exploring the Phenomenonmentioning
confidence: 99%
“…Further, it was found that even though farmer movements and environmentalists concerns propagated the policy level changes (Zygmont, 2000), the real impetus that drove farmers to adopt organic farming practices was largely driven by consumer demands (Rehber and Turhan, 2002).Hence, it is critical to understand the consumers who are committed organic consumers.…”
Section: Organic Food Consumption: Exploring the Phenomenonmentioning
confidence: 99%
“…The main challenges here are inadequate production practices, foreign certification agencies and inadequate retail and logistic support (Rehber and Turhan, 2002).…”
Section: Organic Food Consumption: An Emerging Market Opportunity?mentioning
confidence: 99%
“…Consumers have difficulty distinguishing between genuine organic and other "clean" products [1][2][3][4]. Vietnam is one of the most dynamic emerging countries in the East Asia region, with a gross domestic product (GDP) growth rate of 6.8% in 2017.…”
Section: Introductionmentioning
confidence: 99%